Structural identification of catalytic His158 of PtMAC2p from Pseudozyma tsukubaensis, an acyltransferase involved in mannosylerythritol lipids formation - Nakamichi, Yusuke; Saika, Azusa; Watanabe, Masahiro; Fujii, Tatsuya; Morita, Tomotake (Frontiers in Bioengineering and Biotechnology, 2023)
Mannosylerythritol lipids (MELs) are extracellular glycolipids produced by the basidiomycetous yeast strains. MELs consist of the disaccharide mannosylerythritol, which is acylated with fatty acids and acetylated at the mannose moiety. In the MEL biosynthesis pathway, an acyltransferase from Pseudozyma tsukubaensis, PtMAC2p, a known excellent MEL producer, has been identified to catalyze the acyl-transfer of fatty acid to the C3'-hydroxyl group of mono-acylated MEL; however, its structure remains unclear. Here, we performed X-ray crystallography of recombinant PtMAC2p produced in Escherichia coli and homogeneously purified it with catalytic activity in vitro. The crystal structure of PtMAC2p was determined by single-wavelength anomalous dispersion using iodide ions. The crystal structure shows that PtMAC2p possesses a large putative catalytic tunnel at the center of the molecule. The structural comparison demonstrated that PtMAC2p is homologous to BAHD acyltransferases, although its amino acid-sequence identity was low (<15%). Interestingly, the HXXXD motif, which is a conserved catalytic motif in the BAHD acyltransferase superfamily, is partially conserved as His158-Thr159-Leu160-Asn161-Gly162 in PtMAC2p, i.e. D in the HXXXD motif is replaced by G in PtMAC2p. Site-directed mutagenesis of His158 to Ala resulted in more than 1,000-fold decrease in the catalytic activity of PtMAC2p. These findings suggested that His158 in PtMAC2p is the catalytic residue. Moreover, in the putative catalytic tunnel, hydrophobic amino acid residues are concentrated near His158, suggesting that this region is a binding site for the fatty acid side chain of MEL (acyl acceptor) and/or acyl-coenzyme A (acyl donor). To our knowledge, this is the first study to provide structural insight into the catalytic activity of an enzyme involved in MEL biosynthesis.